Novel compounds protect auditory hair cells against gentamycin-induced apoptosis by maintaining the expression level of H3K4me2 - Ao Li; Dan You; Wenyan Li; Yingjie Cui; Yingzi He; Wen Li; Yan Chen; Xiao Feng; Shan Sun; Renjie Chai; Huawei Li (Drug Delivery, 2018)
Aminoglycoside-induced hair cell (HC) loss is a major cause of hearing impairment, and the effective prevention of HC loss remains an unmet medical need. Epigenetic mechanisms have been reported to be involved in protecting cochlear cells against ototoxic drug injury, and in this study we developed new bioactive compounds that have similar chemical structures as the epigenetics-related lysine-specific demethylase 1 (LSD1) inhibitors. LSD1 inhibitors have been reported to protect cochlear cells by preventing demethylation of dimethylated histone H3K4 (H3K4me2). To determine whether these new compounds exert similar protective effects on HCs, we treated mouse cochlear explant cultures with the new compounds together with gentamycin. There was a severe loss of HCs in the organ of Corti after gentamycin exposure, while co-treatment with the new compounds significantly protected against gentamycin-induced HC loss. H3K4me2 levels in the nuclei of HCs decreased after exposure to gentamycin, but H3K4me2 levels were maintained in the presence of the new compounds. Apoptosis is also involved in the injury process, and the new compounds protected the inner ear HCs against apoptosis by reducing caspase-3 activation. Together, our findings demonstrate that our new compounds prevent gentamycin-induced HC loss by preventing the demethylation of H3K4me2 and by inhibiting apoptosis, and these results might provide the theoretical basis for novel drug development for hearing protection.